Wave hindcast in the North Pacific area considering the propagation of surface disturbances. (July 2018) - Hisaki, Yukiharu
Highlights: A time interpolation method considering the propagation of surface disturbances was demonstrated. The impact of the new time interpolation method on wave prediction was investigated. The improvement of wave height and period prediction was statistically significant. Abstract: Ocean surface waves in the North Pacific area are affected by storm winds. It is necessary to consider the movement of storms to predict waves. The impact of a time interpolation method for winds that considers the propagation of surface disturbances on ocean wave prediction from 2005 to 2006 in the North Pacific area is demonstrated. It is possible to interpolate surface winds, even when there are multiple cyclones and anticyclones moving in different directions at different distances. This method will be useful for wind fields with increasing amounts of spatial information. The predicted wave heights and periods from the linearly interpolated winds and the winds predicted using this new method are compared with in-situ observations from several moored buoys. The predicted wave heights are also compared with those from several drifting buoys in the northwestern Pacific. The improvement of the wave height and period prediction is evident in the case where the difference in the predicted wave parameters between the linear interpolation and the present method is large. The improvement of the wave height and period prediction is statistically significant at more than 95% in most cases. It is shown that the wave height and period prediction can be improved by improving the time interpolation method; however, the improvement of the wave direction prediction is not evident.